Community-based planning in a dynamic landscape development; a teaching experiment - van der Knaap, Wim (AESOP, 2015)
In a four-week studio, second-year bachelor students get acquainted with an approach for an operational plan in a Problem Based Learning Environment. In the course set-up each student represents a stakeholder. Based on input, ideas and vision from stakeholders students try to create a development plan and process, after a landscape analysis and supported by a societal cost-benefit analysis. The students act and think as a (front stage) stakeholder but in the meanwhile doing (backstage) research and analyses, discussing and reporting from an academic point of view. This year, the Brainport Park Cooperative (BPC) in Eindhoven is central. The challenge in this year’s studio is to mimic a community-based planning approach, central in the BPC approach. A core objective of the BPC is to offer space for development to all entrepreneurs, citizens or whoever wants to start and continue this to be beneficial for the community and for the landscape. The landscape is the theatre to host and induce developments. The community of citizens, entrepreneurs, visitors, NGO’s, etc. are the actors. The (local) government should only restrict themselves to facilitate the necessary legal aspects. Because of the available four weeks it will be a pressure cooker situation; the students are either a representative of stakeholders, or one of the (key-)players in the area, with their own ideas and approaches. Are they capable while being a (relative) outsider of the area to be part of that community? Will they have impact on the area development? Is there a community-based planning framework to be applied related to a dynamic landscape development?
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015